Relationship between sleep postures and sleep‐disordered breathing parameters in people with Down syndrome in Japan. Issue 4 (8th April 2015) - Rahmawati, Anita; Chishaki, Akiko; Ohkusa, Tomoko; Sawatari, Hiroyuki; Hashiguchi, Nobuko; Ono, Junji; Kuroda, Hiromi; Nishizaka, Mari K; Ando, Shin‐ichi
Abstract People with Down syndrome (DS) are prone to develop sleep‐disordered breathing (SDB), especially obstructive sleep apnea (OSA) and they are reported to sleep in unusual sleep postures. The purpose of this study was to determine the relationship between sleep postures and SDB parameters, including the objective nocturnal oxygen desaturation in people with DS in Japan. Overnight pulse oximetry was measured in 32 people with DS (male 44%, mean age 18 ± 10 years) and a questionnaire was completed to obtain information on sleep postures and OSA‐related symptoms. Subjects were divided by their dominant sleep postures into three groups: usual postures (supine and lateral), prone, and unusual postures (leaning forward and sitting). Subjects who slept mainly in unusual postures were younger (9.6 ± 5.0 years) than those who slept in prone (18.6 ± 12.4 years) and in usual postures (21.1 ± 8.9 years) (P < 0.05). Snoring was the most reported symptom (81.3%) and was the only symptom positively correlated with 4% oxygen desaturation index (ODI) (r = 0.386, P < 0.05). There was no significant association between 4% ODI and sleep postures among the three groups. DS children with prone and unusual sleep postures had significantly better 4% ODI and minimum SpO2 level compared with those of usual postures (P < 0.05). Our results indicated that prone and unusual sleep postures in DS children might be compensation to alleviate against SDB. These postures could be related to alleviation of SDB resulting from the immaturity of people with DS.